2017
DOI: 10.3847/1538-4357/aa8a6d
|View full text |Cite
|
Sign up to set email alerts
|

Star Formation in the Local Universe from the CALIFA Sample. II. Activation and Quenching Mechanisms in Bulges, Bars, and Disks

Abstract: We estimate the current extinction-corrected Hα star formation rate (SFR) of the different morphological components that shape galaxies (bulges, bars, and disks). We use a multicomponent photometric decomposition based on Sloan Digital Sky Survey imaging to Calar Alto Legacy Integral Field Area Integral Field Spectroscopy (IFS) datacubes for a sample of 219 galaxies. This analysis reveals an enhancement of the central SFR and specific SFR (sSFR=SFR/M å ) in barred galaxies. Along the main sequence, we find t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
53
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 117 publications
(153 reference statements)
11
53
1
Order By: Relevance
“…When accounting for all non-H II mechanisms (the rightmost column), median f non-H II is no higher than 20% (mostly below 10%) for disks across all stellar mass bins, and increases to several tens of percent in bulges when log(M * /M e ) exceeding 10. The result is consistent with the study based on a 2D spectral decomposition of the bulge and disk component (Catalán-Torrecilla et al 2017). The high f non-H II of the bulge is presumably due to the fact that the non-H II sources (e.g., AGNs, evolved stars, and shocks) are naturally found most often in this old central component.…”
Section: Quantitative Contribution Of Non-h II Powering Sourcessupporting
confidence: 81%
See 1 more Smart Citation
“…When accounting for all non-H II mechanisms (the rightmost column), median f non-H II is no higher than 20% (mostly below 10%) for disks across all stellar mass bins, and increases to several tens of percent in bulges when log(M * /M e ) exceeding 10. The result is consistent with the study based on a 2D spectral decomposition of the bulge and disk component (Catalán-Torrecilla et al 2017). The high f non-H II of the bulge is presumably due to the fact that the non-H II sources (e.g., AGNs, evolved stars, and shocks) are naturally found most often in this old central component.…”
Section: Quantitative Contribution Of Non-h II Powering Sourcessupporting
confidence: 81%
“…On the other hand, the quiescent population, primarily composed of bulge-dominated galaxies (e.g., Wuyts et al 2011), has a much lower specific star formation rate (sSFR≡SFR/M * ) with respect to the main sequence. Several studies have suggested that the mainsequence relation flattens at the high-mass end, possibly due to the growth of the bulge, which lowers the global sSFR of a galaxy (Noeske et al 2007;Abramson et al 2014;Whitaker et al 2015;Catalán-Torrecilla et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, whereas in the local universe star formation (SF) is almost omnipresent in low-M ,B , low-Σ ,B bulges, it is steeply vanishing above a characteristic mass-density threshold log(M, Σ) c (10,9), as documented through multi-band photometry (e.g., Peng et al 2010;Omand et al 2014), single-aperture spectroscopy (e.g., Kauffmann et al 2003;Brinchmann et al 2004) Article number, page 1 of 7 arXiv:2001.05738v1 [astro-ph.GA] 16 Jan 2020 A&A proofs: manuscript no. age_gradients_15Jan20 and, more recently, spatially resolved integral field spectroscopy (IFS; e.g., Fang et al 2013;Catalán-Torrecilla et al 2017;Ellison et al 2018;Woo & Ellison 2019, BP18). For instance, Zibetti et al (2017) report from an analysis of stellar indices for 394 galaxies from the CALIFA IFS survey (Sánchez et al 2012) a bi-variate distribution of galaxy stellar populations on the Σ vs. luminosity-weighted age t /yr L plane, with old (log t L 10) quiescent E&S0 galaxies populating a high-density peak (log(Σ ) ≥ 8.3), whereas younger (log t L ≤ 9.5) LTGs being confined to log(Σ ) ≤ 8.…”
Section: Introductionmentioning
confidence: 99%
“…These include, e.g., i) the analysis of radial specific SFR (sSFR) profiles, obtained from Hα and EW(Hα) determinations (e.g. Catalán-Torrecilla et al 2017;Belfiore et al 2018), age-dating of stellar populations via ii) broad-band colors (e.g., Peletier & Balcells 1996;de Jong 1996;Peletier & de Grijs 1998;Muñoz-Mateos et al 2007) or iii) Lick indices (e.g. Thomas & Davies 2006;Morelli et al 2016), and iv) full spectral synthesis of IFS data (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This work represents the extension of their previous work using long-slit spectra (Johnston et al 2012(Johnston et al , 2014 to the IFS case. Other spectro-photometric methods, including the possibly different kinematic distribution of the galaxy components, have also been developed (Coccato et al 2011;Tabor et al 2017;Catalán-Torrecilla et al 2017;Coccato et al 2018).…”
Section: Introductionmentioning
confidence: 99%